Evaluating approaches to EAL newcomer support: protocol for a systematic review. - Murphy, V (2021)
Background There has been an influx of students in the United Kingdom, Australia, Canada, and Ireland who arrive in the country without adequate English skills to fully participate in school. Governments and schools utilised a variety of methods to cater to these newcomer students. Across the aforementioned countries, numerous different approaches to English as an Additional Language (EAL) provision. These can be best categorised as placing newcomers in the mainstream classes (mainstreaming model) or withdrawing them for separate, isolated provision (withdrawal model). Research is lacking on the relative effectiveness of these two different models of newcomer EAL provision.